PENGARUH PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) DENGAN MODEL PROBLEM BASED LEARNING (PBL) DAN PERSEPSI SISWA TERHADAP MATHEMATICAL LITERACY DI SMP - Buyung . (Universitas Batanghari Jambi, 2017)
Abstract: The study is an experimental research by using quasi experimental design. The subject of the study is Grade VIII F and VIII E, amounted to 80 students. The research instruments were, 1) Contextual Teaching And Learning (CTL) Approach Design with Problem Based Learning (PBL) Model, and conventional design, 2) Questionnaire of Perception, 3) assessment mathematical literacy in a form of cognitive test, affective and psychomotor. Analysis Covarian (ANCOVA) as the data analysis. After analyzing the result of the study with ANCOVA, the summaries are 1) there’s Influence students perception toward mathematics toward mathematical literacy; 2) there’s a student mathematical literacy gap taught with Contextual Teaching And Learning (CTL) Approach and Problem Based Learning (PBL) Model, which is higher than students taught by conventional way.Key Words: Contextual Teaching And Learning (CTL) Approach, Problem Based Learning (PBL) Model, Student Perception, Mathematical Literacy